QR-code based real-time interactive learning in iOS - Teng, Shi Xuan (2019)
The final year project titled “QR-Code Based Real-Time Interactive Learning in iOS” aims to develop a mobile application for Apple iOS Devices (iPhone, iPad) to enhance the learning methods, in-class participation, engagement and interaction between the lecturer and the students. Due to the fact that there is lack or no interaction during lecture and tutorial sessions.